OPTIMALISASI PENERAPAN KONSEP ANDRAGOGI DALAM PENDIDIKAN DAN LATIHAN APARATUR PEMERINTAH SEBAGAI UPAYA PENINGKATAN MUTU LULUSAN - Hiryanto Hiryanto (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
The Government could perform its functions and tasks if it has qualified personnel. To improve its personnel’s competence, the Government has been conducting several kinds of training which have not brought satisfactory results. This research aimed at exploring the possibility of implementing andragogic concept in a training model to improve the training graduates’ competence. This case study was conduced in The Education and Training Center of Yogyakarta Province and found an andragogy-based training model with detailed steps. Anticipating some hindrances that could be faced by the trainers in implementiation of this model, this research recommended some alternative solutions.